2012
DOI: 10.3109/17453674.2012.720118
|View full text |Cite
|
Sign up to set email alerts
|

Good function after shoulder arthroplasty

Abstract: Background and purpose Different results after shoulder arthroplasty have been found for different diagnostic groups. We evaluated function, pain, and quality of life after shoulder arthroplasty in 4 diagnostic groups.Patients and methods Patients with shoulder arthroplasties registered in the Norwegian Arthroplasty Register from 1994 through 2008 were posted a questionnaire in 2010. 1,107 patients with rheumatoid arthritis (RA), osteoarthritis (OA), acute fracture (AF), or fracture sequela (FS) returned compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…7 Relief of pain was the main improvement reported. There was minimal improvement in functional range of movement.…”
Section: Discussionmentioning
confidence: 96%
“…7 Relief of pain was the main improvement reported. There was minimal improvement in functional range of movement.…”
Section: Discussionmentioning
confidence: 96%
“…A more detailed description of patients and methods can be found in our previous publication from the same survey [10].…”
Section: Methodsmentioning
confidence: 99%
“…TSA is frequently performed for end-stage arthritis of the shoulder, due to rheumatoid arthritis (RA), osteoarthritis (OA), fracture, or other shoulder disorders [1][2][3][4]. TSA is associated with reduction in shoulder pain and improvement in shoulder function and quality of life [1,[5][6][7] and high patient satisfaction [8]. A recent study that used the 1993-2007 US Nationwide Inpatient Sample (NIS) reported that Blacks had lower overall TSA utilization rates compared to Whites with a risk ratio of 0.6 [9].…”
Section: Introductionmentioning
confidence: 99%